(untitled) (Biological Sciences - PJSIR, 2009)
Chaetomium has a potential source of xylanase and cellulase enzymes, both of which are required in the treatment of fibre in the poultry feed. The titre of the enzymes needs to be enhanced by using recombinant DNA technology for fulfilling the requirement of the industries. Efforts are made to construct prokaryotic and eukaryotic expression cassettes that can be cloned under specific strong promoters i.e., T7 and AOX1, respectively, and the enhancer elements to get the maximum gene expression. In the present study BL21 E. coli and GS115 Pichia pastoris strains are used as model organisms to express the CtX 11-A gene in the presence of 1 mM IPTG and 100% methanol upto final concentration of 0.5. In case of BL21 expression, the maximum xylanase activity was observed after 1.5 h in the presence of 1% xylose, which was 2.302 U/ml and after 7 h in the presence of 0.5% lactose, was 1.708 U/ml. However, in Pichia pastoris the maximum production of xylanase was 2.904 and 0.006 U/ml as compared to control 0.484 and 0.06 U/ml, respectively.